KEMAMPUAN LITERASI MATEMATIS MAHASISWA PROGRAM STUDI MANAJEMEN UNIVERSITAS PEMBANGUNAN PANCA BUDI-MEDAN - Irvan Malay (MES: Journal of Mathematics Education and Science, 2023)
Educational demands on a person's ability in the field of mathematics are not enough just to have the ability to count, but also to have the ability to think logically, systematically and critically in an effort to develop mathematical problem solving abilities. To be able to find a solution to a problem, it is very important for students to be able to dig up information from various sources and various forms of information and interpret it using logical, systematic, and critical mathematical thinking skills, which are then known as mathematical literacy skills. The purpose of this study was to determine the ability of mathematical literacy in management study program students at the Panca Budi Development University in Medan. This research is part of a type of qualitative research with the approach used in this study a descriptive approach with a sample of 30 students who were selected randomly. The instrument used is a test of mathematical literacy skills in basic mathematics courses. The data analysis technique used is descriptive analysis of the data collected. Based on the research results obtained, it can be concluded that the mathematical literacy skills of the management study program students at the Panca Budi Brada Development University are in the sufficient category with the dominant mathematical literacy ability being at a moderate level with a percentage of 43.34%.